2018
DOI: 10.1155/2018/6052326
|View full text |Cite
|
Sign up to set email alerts
|

Oral Manifestations of Systemic Lupus Erythematosus Patients in Qatar: A Pilot Study

Abstract: Objective The purpose of this pilot study was to assess the prevalence of oral manifestations among systemic lupus erythematosus (SLE) patients in Qatar, in order to warrant future studies that would investigate each one of these manifestations with detail and further scrutiny. Methods Study procedures took place between November 2014 and April 2016. All patients visiting the outpatient rheumatology clinics at Hamad General Hospital, Doha, Qatar, were asked to join. The American College of Rheumatology (ACR) 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
6

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
1
26
0
6
Order By: Relevance
“…Cytokine receptors and antibodies stimulate bone resorption by directly inducing proliferation of osteoclast progenitors and also inducing osteoclast maturation. 25,26 Prevalent theories concerning SLE patients believe that cytokines and antibodies are correlated with disease activity, and are also associated with a possible role in periodontitis. Cytokine serum levels were changing in adolescents with SLE compared with healthy subjects and correlated positively with the SLE activity index.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine receptors and antibodies stimulate bone resorption by directly inducing proliferation of osteoclast progenitors and also inducing osteoclast maturation. 25,26 Prevalent theories concerning SLE patients believe that cytokines and antibodies are correlated with disease activity, and are also associated with a possible role in periodontitis. Cytokine serum levels were changing in adolescents with SLE compared with healthy subjects and correlated positively with the SLE activity index.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well established that lupus may lead to dysfunction of multiple organs [26], few studies have investigated association with periodontal disease [26,27] and none have examined mandibular bone mineral density using MCI assessment. To our knowledge, this is the first investigation using the mandibular cortical index in this group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that patients with lupus have a higher risk [26,32] or prevalence [27] of periodontal disease and have suggested that periodontal disease seems to develop earlier [33]. However, other studies using clinical examination had contradictory results and concluded that rates of periodontal disease are similar in patients with lupus and healthy patients [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies indicate that SLE has a prevalence of 30 to 50 cases per 100,000 inhabitants and its incidence ranges from 0.9 to 3.1% per 100,000 inhabitants per year. Women between 30 and 40 years of age are the most affected, with a 10:1 ratio to men (8,10).…”
Section: Characterizationmentioning
confidence: 99%